Prognostic significance of novel serum biomarkers in patients with acute coronary syndrome. (14th October 2021) - Karagiannidis, E; Moysidis, D; Papazoglou, A; Panteris, E; Deda, O; Sofidis, G; Stalikas, N; Otountzidis, N; Ballouri, I; Gavana, E; Gerou, S; Gika, H; et al.
Abstract: Background: As oxygen and nutrient supply to the myocardium significantly decrease during ischemic periods, important changes occur regarding myocardial intermediary energy metabolism and metabolomic biomarkers. Purpose: To identify patients at high risk for adverse cardiovascular (CV) events based on their metabolic signatures through combining clinical characteristics with established and novel biomarkers. Hence, we investigated the prognostic significance of protein biomarkers associated with CAD, namely Galectin-3, Adiponectin, Neutrophil gelatinase-associated lipocalin (NGAL) and Apolipoprotein B and A-1 (ApoB and A-1). Methods: We conducted a sub-analysis of the Corlipid trial (NCT04580173) including patients who underwent coronary angiography in the cardiac catheterization laboratory of an academic tertiary hospital. Venous fasting blood samples were collected prior to coronary angiography and patients were followed-up for 12 months to record the occurrence of major adverse CV events. Galectin-3, adiponectin, NGAL and ApoB/A-1 ratio were measured by enzyme-linked immunosorbent assay (ELISA) in patients' venous blood samples. Serum concentrations were compared among CAD patient subgroups to assess the prognostic significance of these novel protein biomarkers in terms of cardiovascular mortality. Receiver operating characteristic (ROC) curves were also performed to calculate the corresponding area under the curve (AUC) for each biomarker and define their prognostic validity for patients with CAD. Results: Out of 1140 total participants of the CorLipid trial, 534 patients with acute coronary syndrome (ACS) were finally included in the present analysis. Of them, 222 suffered from STEMI, 170 from NSTEMI and 141 from unstable angina. Higher ApoB/ApoA-1 and Galectin-3 serum concentrations were significantly linked with higher incidence of CV death in patients with NSTEMI during the one-year study follow up (p=0.049 and 0.027, respectively). Generated AUC of 0.713 (p=0.047) and 0.775 (p=0.002) indicate a potential utility in the quantification of those proteins as predictors of CV death in patients with NSTEMI. Analysis of serum adiponectin values did not yield any significant outcome (p>0.05). Lower NGAL concentrations were significantly correlated with CV death in patients with STEMI (p<0.001). The corresponding AUC of 0.824 (p=0.003) demonstrated that NGAL could be a prognostic biomarker of great sensitivity and specificity, potently capable to identify STEMI patients with increased risk of CV mortality. Conclusion(s): In patients with ACS, higher values of serum ApoB/ApoA-I and Galectin-3, as well as low NGAL concentrations were associated with higher prevalence of CV death in specific patient subgroups. Therefore, these serum biomarkers could be utilized for early risk-stratification and a more individualized approach in patients with ACS. Larger trials are warranted to confirm and bolster the significance and generalizability of our findings. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): The specific project has been co-financed through the call for Proposals for the Action "Competitiveness, entrepreneurship & innovation" in the framework of the Operational Programme "Research, Create, Innovate" (project code: T1EDK-04005) of the Partnership Agreement for the Development Programme 2014-2020 by the European Social Fund (ESF) and Greek National funds. The project has undergone peer review and has been approved for funding, being awarded a grant of €873, 821.00. The funder had no role in the design or conduct of the study, preparation, review or approval of the manuscript and decision to submit the manuscript for publication.